Rural Resilience in Cancer Survivors: Conceptual Analysis of a Global Phenomenon - Veronica Bernacchi; Jamie Zoellner; Jess Keim-Malpass; Pamela DeGuzman (Rural Nurse Organization; Binghamton University, 2021)
Aim: The aims of this analysis are to (1) identify the concept of rural resiliency in cancer survivors in the nursing literature and (2) propose a conceptual framework that may help nurses leverage rural resilience to improve survivorship care. Background: Rural cancer survivors demonstrate rural resiliency by utilizing aspects of rural culture to improve their psychosocial distress. However, resiliency in rural cancer survivors is poorly understood. Design: We used Walker & Avants' concept analysis approach to direct article selection, review, and analysis. Review methods: We identified a definition, antecedents, consequences, attributes, empirical referents, and related terms, and provide model, contrary, and borderline case examples. Results: We identified 29 articles that met inclusion criteria. We propose a conceptual model of rural resiliency that is grounded in three domains of rural culture: spirituality, cultural norms, and social capital. Attributes of rural culture within these domains impact a cancer survivor's psychosocial health, leading to either negative or positive psychosocial outcomes. Conclusion: A better understanding of how rural resiliency impacts cancer survivors can help clinicians and researchers provide culturally-targeted post-treatment interventions. Our proposed conceptual framework may guide nurse researchers to develop measurement tools that evaluate rural resilience and its impact on health outcomes. Keywords: rural, cancer survivor, resilience, concept analysis, conceptual framework DOI: https://doi.org/10.14574/ojrnhc.v21i1.676